E-COMMERCE UNTUK PEMASARAN PRODUK USAHA KECIL DAN MENENGAH - Dewi Shanti Nugrahani (SEGMEN Jurnal Manajemen dan Bisnis, 2011)
The development of Information Technology which is used by a business is called e-commerce. E-commerce is not only used by abig company but also used by the doer of Small and Medium Enterprise (SME). E-commerce is the one of methods which is used by the doer of Small and Medium Enterprise (SME) to market their products. By using e-commerce, the marketing of Small and Medium Enterprise (SME) products can be widespread so Small and Medium Enterprise (SME) can obtain bigger profit. Keywords : e-commerce, product marketing, Small and Medium Enterprise